Resolving Public Negative Sentiment Towards Taxation in Indonesia According to Abu Yusuf's Thought - Hisnidah, Mukaromatul; Khusnudin (MALIA: Jurnal Ekonomi Islam, 2024)
The issue of tax increases has triggered negative sentiments and strong criticism from the public. This negative sentiment is fueled by concerns about adding to the economic burden on society. On the other hand, public trust in the management of taxation in Indonesia has not yet developed optimally. This study aims to explore ways to enhance public trust in Indonesia's tax management based on the thoughts of Abu Yusuf as outlined in Kitab al-Kharaj. This qualitative research employs a literature review approach by examining Abu Yusuf's perspectives. The findings suggest the need for tax reforms, such as tax collection based on taxpayers' ability (muqasamah), limiting the use of the self-assessment system (qabalah), optimizing agricultural taxes (kharaj), implementing customs duties (usyur), and implementation of mining taxes.